ワークショップ 「2001/2002ネン ナンキョクカイ フクセン ジケイレツ カンソク データカンリ オヨビ セイカ トリマトメ」 ホウコク - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mitsuo (2003)
P(論文) ワークショップ「2001/2002年南極海複船時系列観測データ管理及び成果取りまとめ」を、国立極地研究所講義室において2002年12月4日に開催した。参加者は26名であった。2001/2002年南極海複船時系列観測は、「オーロラ・オーストラリス号」、「白鳳丸」、第43次日本南極地域観測隊(JARE-43)の傭船した「専用観測船(タンガロア号)」、及びJARE-43「しらせ」によりなされた。各航海概要とデータ取得状況が報告された後、その管理及び成果取りまとめについて議論した。 A Workshop "Data management and synthesis of the results obtained during multi-ship/time-series study in 2001/2002 austral summer" was held on 4th December 2002 at the National Institute of Polar Research (NIPR), Tokyo, with 26 participants. The multi-ship/time-series study of the Antarctic Ocean was achieved by RSV Aurora Australis, RV Hakuho Maru, RV Tangaroa chartered by the 43rd Japanese Antarctic Research Expedition (JARE-43) and Icebreaker Shirase of JARE-43. The current status of data was reported. Data management and synthesis of scientific results obtained during the cruises were discussed. departmental bulletin paper